Evaluasi Penataan Interior Kelas Terhadap Pembentukan Perilaku Anak di KBTK Islam Sakha Sidoarjo - Mega Ayundya Widiastuti (Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
Early childhood education is an essential stage for the development of children's ability to attend school. Early age is the best phase for children to receive stimulation as well as their character formation in the future. The physical environment plays a vital role in supporting the successful establishment of children's behavior. One of them is through the design of classrooms that are suitable for the child's world. This study attempted to evaluate the interior arrangement of the school in the formation of children's behavior along with its influence on children's behavior in the Sakha Islamic Play Group / Kindergarten. This study uses a descriptive method with a qualitative approach and observation techniques on various aspects of the class physical arrangement. The results of the study concluded that some elements of the interior provision of classes in the Sakha Islamic Play Group / Kindergarten, such as the visibility and comfort, were not in accordance with the standards, while the classroom interior arrangement had influenced the children's behavior with the barrier mechanism and invited some specific children behaviors to shape their personality.